MiR-19 Is a Potential Clinical Biomarker for Gastrointestinal Malignancy: A Systematic Review and Meta-analysis. (10th September 2020) - Song, Xiaoxu; Li, Wenyi; Shen, Peng; Bai, Bing; Cao, Lin-Lin
Abstract : Objectives . To assess the expression and clinical value of miR-19 in gastrointestinal malignancy. Setting . Embase, Web of Science, PubMed, and other databases were retrieved to screen out relevant studies until December 31, 2019. Participants . Gastrointestinal cancer patients with the description of miR-19 expression, as well as the correlation between miR-19 and clinicopathological characteristics or prognosis. Main Outcome Measures . Pooled odds ratio (OR) or hazard ratio (HR) with 95% confidence interval (CI) was obtained to determine miR-19 expression in gastrointestinal malignancy and the association between miR-19 and patients' clinical characteristics and survival. Results . Thirty-seven studies were included in this study. miR-19 levels in gastrointestinal malignancy, especially in hepatocellular (OR = 4.88, 95 % CI = 2.38 ‐ 9.99 ), colorectal (OR = 4.81, 95 % CI = 2.38 ‐ 9.72 ), and pancreatic (OR = 5.12, 95 % CI = 2.43 ‐ 10.78 ) cancers, were significantly overexpressed, and miR-19 was tightly related to some clinicopathological characteristics, such as lymph node metastasis (OR = 1.74, 95 % CI = 1.05 ‐ 2.86 ). Although gastrointestinal cancer patients with low and high miR-19 expression had comparable OS (overall survival) and DFS (disease-free survival), subgroup analyses showed that patients with high miR-19 presented better DFS than those with low miR-19 in liver cancer (HR = 0.46, 95 % CI = 0.30 ‐ 0.71 ). Conclusions . miR-19 might be a potential progression and prognostic biomarker for gastrointestinal malignancy.